Two-component signaling systems. - Simon, Melvin I.; Crane, Brian R.; Crane, Alexandrine (Methods in enzymology, 2010)
Multicellular organisms must be able to adapt to cellular events to accommodate prevailing conditions. Sensory-response circuits operate by making use of a phosphorylation control mechanism known as the "two-component system." This volume, the third in a three-volume treatment edited by the same group of editors, includes a wide range of methods, including those dealing with the Sln-1 kinase pathway, Triazole sensitivity in C. albicans, and Histidine kinases in cyanobacteria circadian clock. * Includes time-tested core methods and new innovations applicable to any researcher studing two-component signaling systems or histidine kinases * Methods included are useful to both established researchers and newcomers to the field * Relevant background and reference information given for procedures can be used as a guide to developing protocols in a number of disciplines